THE CORRELATION BETWEEN STUDENTS' LEXICAL KNOWLEDGE OF COLLOCATIONS AND THEIR READING COMPREHENSION(A STUDY OF THE SIXTH SEMESTER STUDENTS OF ENGLISH LITERATURE PROGRAMAT INDONESIA UNIVERSITY OF EDUCATION) - Yana Pardiana, - (2008)
The study investigates the knowledge of English lexical collocations and their relation to reading comprehension of Indonesian EFL university students. Data for the study were collected from 30 English Literature Students of Indonesia University of Education (UPI). Each student was asked to take two tests: (1) one lexical collocation test, measuring the students' knowledge of lexical collocations; (2) one English reading comprehension test, measuring the students' level of mastery of reading comprehension. Test results were compared to find out the correlation between those variables. The findings showed that there was a significant correlation between Indonesian EFL students' knowledge of collocation and their reading comprehension. The current study concludes that knowledge of lexical collocation seemed to give significant contribution to the understanding of the discourse on the reading.